Clinical effects of Emblica officinalis fruit consumption on cardiovascular disease risk factors: a systematic review and meta-analysis - Paul D. S. Brown; Nicole Ketter; Mathew Vis-Dunbar; Brodie M. Sakakibara (BMC, 2023)
Abstract Background Emblica officinalis (EO) fruit consumption has been found to have a beneficial effect on cardiovascular disease (CVD) physiological risk factors in preliminary clinical intervention trials; however, questions remain regarding the overall effectiveness of EO on CVD risk. The purpose of this systematic review and meta-analysis is to: 1) systematically describe the clinical research examining EO; and 2) quantitatively assess the effects of EO on CVD physiological risk factors. Methods The Pubmed, Embase, Web of Science, and Google Scholar electronic platforms were searched for relevant randomized controlled trials (RCTs) published until April 7, 2021. Studies were included if they involved adults (age ≥ 18 years) ingesting a form of EO fruit; included blood lipids, blood pressure, and/or inflammatory biomarkers as outcomes; had clearly defined intervention and control treatments with pre- and post-intervention data; were peer-reviewed; and were written in English. Studies were excluded if they compared EO with another risk reduction intervention without a usual care control group. RCTs were assessed for methodological quality using the Cochrane risk-of-bias version 2 (ROB2) tool, qualitatively described, and quantitatively evaluated using random and fixed effect meta-analysis models. Results A total of nine RCTs (n = 535 participants) were included for review. Included studies followed parallel-group (n = 6) and crossover (n = 3) designs, with EO dosage ranging from 500 mg/day to 1500 mg/day, and treatment duration ranging from 14 to 84 days. Meta-analyses revealed EO to have a significant composite effect at lowering low-density lipoprotein cholesterol (LDL-C; Mean difference (MD) = -15.08 mg/dL [95% Confidence interval (CI) = -25.43 to -4.73], I2 = 77%, prediction interval = -48.29 to 18.13), very low-density lipoprotein cholesterol (VLDL-C; MD = -5.43 mg/dL [95% CI = -8.37 to -2.49], I2 = 44%), triglycerides (TG; MD = -22.35 mg/dL [95% CI = -39.71 to -4.99], I2 = 62%, prediction interval = -73.47 to 28.77), and high-sensitivity C-reactive protein (hsCRP; MD = -1.70 mg/L [95% CI = -2.06 to -1.33], I2 = 0%) compared with placebo. Conclusions Due to statistical and clinical heterogeneity in the limited number of clinical trials to date, the promising effects of EO on physiologic CVD risk factors in this review should be interpreted with caution. Further research is needed to determine if EO offers an efficacious option for primary or secondary prevention of CVD as either monotherapy or adjunct to evidence-based dietary patterns and/or standard pharmacotherapy.